Diligence and Emotion: Knitting in Danish Golden Age Portraiture. (3rd May 2016) - Schram Vejlby, Anna
Abstract: Wealthy ladies knitting provide a recurrent motif of Danish middle-class portraiture of the first half of the nineteenth century. This article explores the cultural and social significance of these images, and how they represent the central values of the Danish Golden Age (c.1810–1850). Since knitting was an essential skill for all women, this motif has traditionally been explained as part of the realist turn in Danish art. This article takes a new approach by arguing that the knitting carries an emotional value which has yet to be discussed by scholars. Displaying socially appropriate emotions was one way in which the middle classes distinguished themselves from the aristocracy and lower classes. On the one hand, sitters remained calm and collected and therefore rational. On the other, they needed to show emotional warmth, which was an obligatory marker of a good citizen. In order to balance the coolness of their expression, the emotional content of portraits was transferred to their material elements. The knitting of stockings in portraits thus became a tactile sign of romantic and maternal love. A young woman knitting for her future husband, or mother making stockings for her children, produced emotionally invested tokens of love. As a key marker of homemade love, the emotional warmth of these Golden Age portraits was carried by knitting as a textile symbol of emotion.